Shame Proneness and Fear of Intimacy Predicting Sexual Avoidance in Couples - Radu, Elena; Morales, Luis (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to investigate the predictive roles of shame proneness and fear of intimacy in explaining sexual avoidance among romantic couples.Methods and Materials: Using a correlational descriptive design, the study sampled 417 adult participants in romantic relationships from Peru, with sample size determined based on the Morgan and Krejcie table. Standardized instruments were used to measure sexual avoidance, shame proneness, and fear of intimacy. Data were analyzed using SPSS-27, applying Pearson correlation to assess the relationships between variables and multiple linear regression to examine the predictive power of the independent variables on sexual avoidance.Findings: Pearson correlation analysis revealed significant positive associations between sexual avoidance and both shame proneness (r = .48, p < .01) and fear of intimacy (r = .62, p < .01). The regression model was statistically significant, F(2, 414) = 161.83, p < .001, with an R² value of .44, indicating that the predictors jointly accounted for 44% of the variance in sexual avoidance. In the multivariate regression, both shame proneness (β = 0.33, t = 5.80, p < .001) and fear of intimacy (β = 0.49, t = 9.44, p < .001) significantly predicted sexual avoidance, with fear of intimacy emerging as the stronger predictor.Conclusion: The findings underscore the substantial influence of psychological factors—particularly fear of intimacy and shame proneness—on sexual avoidance behaviors in couples. These results highlight the need for emotionally focused and vulnerability-informed therapeutic interventions that target underlying emotional barriers to intimacy. Addressing these psychological dimensions may be essential for restoring sexual engagement and relational satisfaction in distressed couples.